Design of robust adaptive AVR - Bhattacharya P.K.; Nagaraja T.; Gandhi B.R.M. (My University, 2025)
Adaptive controller for static exciter system is designed, using the hyperstability conditions, ensuring the asymptotic stability of the designed system. Its effectiveness in the presence of unmodelled plant dynamics, with SPR compensator for robustness, is verified by digital computer simulation. © 1992 by IEEE Singapore Section.